2013
DOI: 10.1002/anie.201303282
|View full text |Cite
|
Sign up to set email alerts
|

Is JmjC Oxygenase Catalysis Limited to Demethylation?

Abstract: Jobs on the side: Substrate selectivity studies indicate that members of the biomedically important JmjC demethylase family of histone Nε‐methyllysine demethylases are capable of catalyzing the de‐N‐alkylation of groups other than N‐methyl and can catalyze reactions that form stable hydroxylated products. The differences in binding preferences in this set of enzymes may be helpful in the design of selective inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 25 publications
(21 reference statements)
2
41
1
Order By: Relevance
“…G9a, in particular, produced significant amounts (55 % after 3 h and 75 % after 5 h) of H3K9meet (Figures A and B and S8). The observation that G9a and GLP have the capacity to catalyze the formation of H3K9meet is interesting because functionally related histone lysine demethylases PHF8, FBXL11, and JMJD2E were found to catalyze the removal of methyl and ethyl groups in H3K9meet; thus producing unmodified H3K9 (a substrate for G9a and GLP) . Moreover, our MALDI‐TOF MS assays revealed that G9a and GLP also catalyzed the ethylation of H3K9me2, producing approximately 25 % of bulky H3K9me2et in the presence of AdoSeEth; only traces of H3K9me2et were observed if AdoEth was used as a cosubstrate (Figure C and D).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…G9a, in particular, produced significant amounts (55 % after 3 h and 75 % after 5 h) of H3K9meet (Figures A and B and S8). The observation that G9a and GLP have the capacity to catalyze the formation of H3K9meet is interesting because functionally related histone lysine demethylases PHF8, FBXL11, and JMJD2E were found to catalyze the removal of methyl and ethyl groups in H3K9meet; thus producing unmodified H3K9 (a substrate for G9a and GLP) . Moreover, our MALDI‐TOF MS assays revealed that G9a and GLP also catalyzed the ethylation of H3K9me2, producing approximately 25 % of bulky H3K9me2et in the presence of AdoSeEth; only traces of H3K9me2et were observed if AdoEth was used as a cosubstrate (Figure C and D).…”
Section: Resultsmentioning
confidence: 82%
“…We then performed comparative enzymatic assays for KMTcatalyzed methylation (with AdoMet) and ethylation (with AdoEth and AdoSeEth) of synthetic histone peptides by using MALDI-TOF MS, as recently described; [10a,b] histone H3 1-15 was used for studies with SETD7 (also known as KMT7), G9a (also known as KMT1C and EHMT2), and GLP (also known as KMT1D and EHMT1), and histone H4 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] was used for studies with SETD8 (also known as KMT5A). MALDI-TOF MS data confirmed that human KMTs catalyzed nearly quantitative methylation of histone peptides in the presence of AdoMet: H3K4me, H4K20me, H3K9me3, and H3K9me3 were formed in the presence of SETD7, SETD8, G9a, and GLP, respectively (Figure 2, top).…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the mechanistically related DNA demethylase, AlkB (discussed below),, a crystal structure of the enzyme bound to this reaction intermediate has been solved, and for the human nucleic acid oxygenase, FTO, the formation of stable hemiaminal products have been observed ,. In addition, work on lysine analogues in our group, see below, has led to observation of a stable β‐hydroxylated alkyl group, further confirming the proposed reaction mechanism . Unlike the KDM1s, which for mechanistic reasons can only act on the mono‐ and dimethylated states, the JmjC KDMs can act on all lysine N ϵ ‐methylation states (including KMe 3 ) .…”
Section: Jmjc Proteins and Ribosomal Oxygenasesmentioning
confidence: 52%
“…For most, but not necessarily all, JmjC KDMs, a positively charged substrate is preferred. The results also revealed that some JmjC KDMs will catalyse hydroxylations to give stable alcohol products (Figure A) . In addition to its mechanistic relevance, this work led us to explore the propensity of JmjC KDMs to catalyse hydroxylation and subsequent demethylation of dimethylated arginyl‐residues, of which the asymmetric form is roughly isosteric with N ϵ ‐methyl,isopropyllysine.…”
Section: Histone Demethylases and Nucleic Acid Oxygenasesmentioning
confidence: 92%
See 1 more Smart Citation